2015
DOI: 10.1016/j.ijpe.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Embeddedness and path dependence of organizational capabilities for mass customization and green management: A longitudinal case study in the machinery industry

Abstract: A growing number of firms today have to cope with the twofold challenge of mass customization (i.e., combining high performance in product customization with high performance in cost, delivery and quality) and green management (i.e., integrating environmental-sustainability principles into businesses). Research on this joint challenge, however, is still limited in the literature. To narrow this gap, we empirically investigate the interconnectedness of mass customization and green management on the level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 97 publications
3
40
0
1
Order By: Relevance
“…This interaction, made possible through BIM models and Web-based application, is part of the MC method that is being developed in this research. The study of Trentin, Forza, and Perin, (2015) found links between MC and sustainability and concluded that research on this subject is still limited. Pedrazzoli et.al., (2011) stated that additional investigations are needed to conclude that MC is a driver for improvement in sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction, made possible through BIM models and Web-based application, is part of the MC method that is being developed in this research. The study of Trentin, Forza, and Perin, (2015) found links between MC and sustainability and concluded that research on this subject is still limited. Pedrazzoli et.al., (2011) stated that additional investigations are needed to conclude that MC is a driver for improvement in sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Pedrazzoli et.al., (2011) suggested that additional investigations are needed to conclude that MC is a driver for improvement in sustainability. The study of Trentin, Forza, and Perin, (2015) found links between MC and sustainability and concluded that research on this subject is still limited. According to Medini, Da-Cunha, and Bernard, (2011), MC and Sustainability need to be assessed together in order to strengthen both of them.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts allowed interviewees to gradually and freely mention the negative aspects of these firms. As the retrospective interviews concerned relatively recent facts [140], the last round of interviews was conducted after 2017. With the time gap, enriched information increasingly emerged.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…For example, Hora et al [13] provide a generic framework proposal with several business model patterns for sustainable MC. Trentin et al [14] empirically investigate how MC and green management are interconnected and conclude that synergies exist between the two paradigms. Fornasiero et al [15] integrate LCA into the supply chain management of customised products to evaluate the sustainability of different options.…”
Section: Sustainable Mass Customisation and Mass Personalisationmentioning
confidence: 99%